Critical evaluation of attosecond time delays retrieved from photoelectron streaking measurements - Wei, Hui; Morishita, Toru; Lin, C. D. (My University, 2016)
A photoelectron streaking experiment which was conceived as a means to extract the electron wave packet of single-photon ionization has also been employed to retrieve time delays in the fundamental photoemission processes. The discrepancies between the time delays thus measured and those from many sophisticated theoretical calculations have generated a great deal of controversy in recent years. Here we present a careful examination of the methods that were used to retrieve the time delays and demonstrate the difficulty of achieving an accuracy of the retrieved time delays of a few to tens of attoseconds in typical streaking measurements. The difficulty owes more to the lower sensitivity of the streaking spectra to the phase of the photoionization transition dipole than to the spectral phase of the attosecond light pulse in the experiment. The retrieved time delay contains extra errors when the attochirp of the attosecond pulse is large so that the dipole phase becomes negligible compared to it.